1996
DOI: 10.1128/jb.178.16.4814-4821.1996
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and nucleotide sequence of the GDP-mannose:cellobiosyl-diphosphopolyprenol alpha-mannosyltransferase gene from Acetobacter xylinum

Abstract: A genetic locus from Acetobacter xylinum involved in acetan polysaccharide synthesis has been characterized. The chromosomal region was identified by screening a genomic library of A. xylinum in a Xanthomonas campestris mutant defective in xanthan polysaccharide synthesis. The A. xylinum cosmid clone can functionally complement a xanthan-negative mutant. The polymer produced by the recombinant strain was found to be indistinguishable from xanthan. Insertion mutagenesis and subcloning of the cosmid clone combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 42 publications
(44 reference statements)
0
16
0
Order By: Relevance
“…The same may be true for the glycosyltransferases from families 4, 5, and 15 of Campbell's classification, although in these cases, experimental confirmation would be required. This type of evidence has been obtained for Ace-A (35,46), an ␣-mannosyltransferase that belongs to family 4. Geremia et al (42) found an E-X 7 -E motif similar to that described here in a group of prokaryotic ␣-mannosyltransferases and proposed that both conserved Glu residues were important for catalysis.…”
Section: Discussionmentioning
confidence: 96%
“…The same may be true for the glycosyltransferases from families 4, 5, and 15 of Campbell's classification, although in these cases, experimental confirmation would be required. This type of evidence has been obtained for Ace-A (35,46), an ␣-mannosyltransferase that belongs to family 4. Geremia et al (42) found an E-X 7 -E motif similar to that described here in a group of prokaryotic ␣-mannosyltransferases and proposed that both conserved Glu residues were important for catalysis.…”
Section: Discussionmentioning
confidence: 96%
“…Since E295A produced very little amounts of polysaccharide, we have used the strain XcH E295G that produces slightly more EPS than XcH E295A. 2 The EPSs produced by strains D109A, H127A, S162A, L270A, and E295G were viscous, indicating the presence of a high molecular weight polysaccharide. The 1 H NMR spectra of D109A, H127A, S162A, and L270A display the characteristic signals of xanthan gum, in particular at ␦ 1.8, 2.1, and 5.2, which correspond to the acetyl, ketal pyruvate and ␣(1-3)-Man moieties (Fig.…”
Section: Fig 3 Subcellular Localization Of Acea In E Coli Bl21 (De3)mentioning
confidence: 99%
“…A large number of genes thought to encode glycosyltransferases involved in the assembly of repeat units have been identified, reflecting the extreme structural diversity of these bacterial polysaccharides. AceA is a non-processive ␣-1,3 mannosyltransferase from Acetobacter xylinum, which transfers mannose from GDP-mannose (GDP-Man) 1 to polyprenyl-pyrophosphate-linked cellobiose (Glc 2 -PP-Lip) during the assembly of the heptasaccharide repeat unit of the exopolysaccharide acetan (2,3). Acetan is structurally related to the widely used exopolysaccharide xanthan gum from Xanthomonas campestris (see Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic analysis of BC showed that the bcs operon is associated with cellulose synthesis. 8) In contrast, the genetics of the acetan biosynthetic process has not been clariˆed 9,10) although the biochemical pathway has been elucidated. [11][12][13][14] Because the production patterns during culture of the two extracellular polysaccharides are similar, we have speculated that there is a relationship between BC and acetan in their productivity; however, to our knowledge, there has been no report on a relationship between acetan and BC biosynthesis.…”
mentioning
confidence: 99%